2016
DOI: 10.1111/jfbc.12248
|View full text |Cite
|
Sign up to set email alerts
|

Antigrowth and Apoptosis Inducing Effects of Hypericum Olympicum L . and Hypericum Adenotrichum Spach. on Lung Cancer Cells In Vitro : Involvement of DNA Damage

Abstract: Hypericum species are used in different folk medicines and screened for their biological activity including cancer. We, therefore, evaluated the possible cytotoxic/ apoptotic and genotoxic activities of Hypericum adenotrichum Spach. and Hypericum olympicum L. Antigrowth effect was screened in human lung cancer cell lines (A549 and PC3) by the ATP viability assay, while genotoxic activity was performed using the Comet assay. Histological and biochemical methods were utilized to elucidate the cell death mode. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Also, a growth inhibitory and programmed cell death inducing effects of H. olympicum subsp. olympicum extract in lung cancer cells was previously reported by our research group (Aztopal et al, 2016).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Also, a growth inhibitory and programmed cell death inducing effects of H. olympicum subsp. olympicum extract in lung cancer cells was previously reported by our research group (Aztopal et al, 2016).…”
Section: Introductionmentioning
confidence: 61%
“…Uludag region in Bursa, Turkey. A methanolic extract from 30 g of the trunk and flowers of this plant was prepared by utilizing a Soxhlet apparatus as previously described (Aztopal et al, 2016). The sample was lyophilized and kept at -20 °C for further use.…”
Section: Extraction and Chromatographic Analysis Of H Olympicum Subsmentioning
confidence: 99%
“…Recently, Li et al [14] examined that Hypericum ascyron extract has cytotoxic activity against different cancer cell lines. In our previously study, we demonstrated that the extract of Hypericum adenotrichum and Hypericum olympicum have cytotoxic activity on lung cancer cells by inducing apoptosis [19]. In this study, we showed that HAE and HOE exhibited significant anti-growth activity against human hepatoma (Hep3B) and rat glioma (C6) cell lines in a dose dependent manner.…”
Section: Hypericum Adenotrichum Hypericum Olympicummentioning
confidence: 70%
“…These results demonstrated that the cells dying by necrosis after the treatment with HAE and HOE. In our previously studies, we found that HAE and HOE have cytotoxic effects by inducing apoptosis in human breast and lung cancer cells [19,20]. In another study, Ozmen et al [39] reported that petroleum ether extract of Hypericum adenotrichum induced apoptosis through on caspase 3 activation and PARP cleavage in HL-60 cells.…”
Section: Hypericum Adenotrichum Hypericum Olympicummentioning
confidence: 99%
See 1 more Smart Citation